PENGARUH CARA PENGEMASAN, JENIS BAHAN PENGEMAS, DAN LAMA PENYIMPANAN TERHADAP SIFAT KIMIA, MIKROBIOLOGI, DAN ORGANOLEPTIK SATE BANDENG (Chanos chanos) - Muhammad Nur (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2009)
Sate bandeng is a perishable product which has a short shelf life time (about 3 day). It is particularly couse by the contamination of the environment. Thus, packaging is need to reduce contamination and retain destruction to prolong the storage time. This research was aimed to determine the best. Packaging technique materials and also maximum storage time so that sate bandeng has chemical, microbial, and organoleptic characteristics which is still consumtable. The result of the research shower that the vacuum packaging with polypropylene was the best treatment with maximum storage time within 6 day with 46,31% of water content; 55,53 mg/100 g of TVN content, total aerobic microbe 2,6x105colony/g, total anaerobic facultative microbe 2,1 x 104colony/g and has rather specific aroma of sate bandeng, compact and hard texture. Meanwhile the total acceptance of the product is rather liked by the panelist. Key words: sate bandeng, vacuum packaging, polypropylene